An Econometric Analysis of Loan Loss Provisioning Behaviour in Indian Commercial Banks - Lam, Tsz Yan (2017)
Given the raising concern on provisioning in the banking industry, this study aims at evaluating the loan loss provisioning behaviour among Indian commercial banks during the years 2007-2016. The study has been carried out in two stages. In the first stage, the cost efficiency of Indian banks is analysed. The second stage analyse the relationship among the four main hypotheses (namely capital management, business cycle, income smoothing and cost efficiency) and loan loss provisions (LLPs). Results of this study indicate that income smoothing and capital management behaviour through LLPs was not prevalent among Indian commercial banks during the period under review. In addition, no significant relationship is found between cost efficiency and LLPs in this study, which shows little evidence on bad management by Indian commercial banks. However, (i) counter-cyclicality; and (ii) a significant and positive relationship between bank size and LLPs are found from analysing the available data.